2018
DOI: 10.1051/0004-6361/201832964
|View full text |Cite
|
Sign up to set email alerts
|

GaiaData Release 2

Abstract: Context. The second Gaia data release (Gaia DR2) provides precise five-parameter astrometric data (positions, proper motions, and parallaxes) for an unprecedented number of sources (more than 1.3 billion, mostly stars). This new wealth of data will enable the undertaking of statistical analysis of many astrophysical problems that were previously infeasible for lack of reliable astrometry, and in particular because of the lack of parallaxes. However, the use of this wealth of astrometric data comes with a speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
632
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(647 citation statements)
references
References 32 publications
15
632
0
Order By: Relevance
“…Restricting ourselves to the confirmed SMC members of our extended data set we end up with 5636 stars with radial velocity determinations and proper motions from Gaia DR2. Due to the distance to the SMC (∼60 kpc) and the faintness of the stars in our extended sample (G magnitude between 15 and 17 for 94% of the sample), the parallaxes from the Gaia DR2 astrometric solution do not give a meaningful constraint on the distance (Arenou et al 2018;Lindegren et al 2018;Luri et al 2018). Since we already selected the SMC members with the radial velocity information, there is no need to rely on distance measurements to remove foreground MW stars.…”
Section: General Considerationsmentioning
confidence: 97%
“…Restricting ourselves to the confirmed SMC members of our extended data set we end up with 5636 stars with radial velocity determinations and proper motions from Gaia DR2. Due to the distance to the SMC (∼60 kpc) and the faintness of the stars in our extended sample (G magnitude between 15 and 17 for 94% of the sample), the parallaxes from the Gaia DR2 astrometric solution do not give a meaningful constraint on the distance (Arenou et al 2018;Lindegren et al 2018;Luri et al 2018). Since we already selected the SMC members with the radial velocity information, there is no need to rely on distance measurements to remove foreground MW stars.…”
Section: General Considerationsmentioning
confidence: 97%
“…As noted by Luri et al (2018), using small relative parallax error quality cuts introduces artifical asymmetries, or biases, into a data set, because the parallax error is a function of position on the sky due to the Gaia scanning law's non-uniform sampling of different regions of the sky. This would irreparably bias the study of symmetries over an appreciable extent of the galaxy, as shown in Fig.…”
Section: Data Selection and Completeness Studiesmentioning
confidence: 99%
“…Here and throughout the paper we use the value of −0.029 mas derived by the Gaia-DR2 team (Lindegren et al 2018). 2 We have added quadratically systematic errors of 0.1 mas for parallax and 0.1 mas yr −1 for proper motions (Luri et al 2018). a radius of 2 .3 of V838 Mon, we find only one candidate in the Gaia DR2 catalog, star 3107789583219504000, which is 6 east of V838 Mon.…”
Section: The Cluster Of V838 Monmentioning
confidence: 99%